Fiscal decentralization in China and India: Competitive, cooperative or market preserving federalism? - Nirvikar Singh (University of California, Economics Department, 2007)
This paper provides a comparative assessment of fiscal decentralization in China and India, including the standard components of expenditure and revenue assignments and institutions for intergovernmental transfers, as well as the nature of subnational authorities over general economic activity. In particular, the case of China, where town and village enterprises have been very active, is contrasted with that of India, where local governments remain circumscribed in their authority, despite decentralizing reforms. The implications of differences in decentralization for fiscal outcomes and economic growth are discussed. The characterization of each country in terms of concepts of federalism, i.e., competitive, cooperative and market preserving federalism, is discussed, in attempting to abstract from the two cases to more general lessons for fiscal decentralization.
Keywords: P26; P35; H1; H7; 330; cooperative federalism; competitive federalism; market-preserving federalism; decentralization; economic development; Finanzföderalismus; Dezentralisierung; China; Indien